Research on the impact of residents’ pension insurance choices based on their cognition of pension responsibility - Lulin Zhou; Wenling Zhu; Yupeng Cui; Yinghua Chen; Xinglong Xu (Frontiers in Public Health)
BackgroundThe aging of the world’s population has become an increasingly serious issue in recent years, and pensions in all countries have become unsustainable to varying degrees. The sustainability of pension insurance is a pressing issue.ObjectiveThis study examined Chinese residents’ cognition of pension responsibility and its impact on their participation in pension insurance under the multi-pillar pension insurance system.MethodsUsing data from the 2021 Chinese General Social Survey, the link between residents’ cognition of pension responsibility and pension insurance participation was investigated through binary regression and disordered multiclassified logistic regression analysis.ResultsFirst, there was a difference in the influence of economic and sociodemographic factors on the choice of basic and commercial pension insurance. Second, “offspring responsibility,” as a dominant perception today, had a negative impact on participation in both basic and commercial pension insurance. The probability of individuals who hold the belief in the “three-party responsibility” participating only in basic pension insurance was significantly higher than that of those who agree with “offspring responsibility” or “self-responsibility.” Third, the relationship between the cognition of pension responsibility and pension insurance participation was moderated by region of residence and people’s access to information.ConclusionThrough system optimization, awareness campaigns, and education, efforts should be made to modernize and transform the concept of pensions, promote the coordinated development of basic and commercial pension insurance, and build a more comprehensive and sustainable multi-level pension security system.